CORRELATION OF ROUTINE URINE CULTURE AND STONE CULTURE TO POST-OPERATIVE SIRS - Indrawan, Taufik; Hardjowijoto, Sunaryo; Soebadi, Doddy M.; Juniastuti, Juniastuti; Budiono, Budiono (Indonesian Urological Association, 2014)
Objective: This study evaluated the correlation between preoperative urine culture and intraoperative stone culture and the impact of stone culture ﬁndings on post-operative systemic inﬂammatory response syndrome. Material & Method:Patients with kidney stones who underwent percutaneous nephrolithotomy (PCNL) from February to May 2012 were prospectively analyzed. A pre-operative urine culture was obtained in the morning before the operation, fragmented stone collected were cultured in Departement of Microbiology. Patients were monitored closely in the postoperative period for signs of systemic inflammatory response syndrome (SIRS). Results:A total of 33 patients underwent PCNL and examined for urine cultures, stone culture and postoperative SIRS, 15 (45.45%) patients with positive urine culture, 18 patients (54.54%) with positive stone culture but only 1 patient (3.03%) had same pathogen (p = 0.629). Ten patients (55.6%) with positive stone cultures had evidence of systemic inflammatory respose syndrome postoperatively. The calculated stone culture value for sensitivity, specificity, positive predictive value and negative predictive value were 100%, 65.2%, 55.6%, and 100%. Preoperative hydronephrosis (p = 0.003) and operative time (p = 0.001) are identified as the key risk factors for SIRS after PCNL.Conclusion: Positive stone culture are better predictors for SIRS after PCNL. Stone culture examination is an essential in directing the proper antibiotic therapyin patients with SIRS after PCNL. Keywords: Percutaneous nephrolithotomy (PCNL), urine culture, stone culture, systemic inflammatory response syndrome after PCNL.